Clonagem e expressão heteróloga da proteína promotora de florescimento - Soares, Natalia Cristina (2023)
Citrus are perennial woody plants and have different stages of development during their life cycle: germination, juvenile stage, growing stage, and reproductive stage. The juvenile stage is characterized by the absence of flowers and fruits that can vary from 6 to 20 years. The flowering process is composed of a complex and synchronized regulatory network that is shared by different species. The citrus CiFT3 gene and tomato SFT gene, homologous to FLOWERING LOCUS T (FT) from Arabidopsis thaliana, encode an universal mobile signal, known as florigen, that is shared among different species. With the recombinant DNA technology, it’s possible to produce proteins through the expression of cloned genes under the control of promoters. These proteins can be purified in order to obtain a pure biologically active molecule. The objective of this project is the expression and purification of the flowering-promoting proteins of citrus and tomato in a heterologous system, in order to enable the application and evaluation of their effects. The CiFT3 and SFT genes were cloned in the vector pET28a, introduced in competent E. coli BL21(DE3) cells and expressed by inducing with different concentrations of IPTG using different times. So far, the recombinant proteins from citrus and tomato have been purified using immobilized metal affinity chromatography. The best condition for the expression was obtained by using 1mM of IPTG at 37ºC under stirring of 200 rpm for 16 hours (Tov). The expression of the recombinant protein was evaluated by SDS-PAGE, which was present in the soluble fraction. The purified CiFT3 protein had yields ranging from 14 to 153 ng/uL, while the purified SFT protein had yields ranging from 18 to 115 ng/uL. Flowering induction tests were performed in vitro, through root absorption with and without vacuum application, and ex vitro, through leaf and apical meristem absorption, in juvenile citrus, tobacco, and tomato plants. The protein concentrations used in the tests varied from 1 ng/μL to 33,600 ng/μL. Induction tests were not successful in promoting early flowering. A possible explanation for this would be the non-effective translocation of the protein from the leaves, where they were injected, to the apical meristem or significant amounts of flowering-promoting proteins may not have been reached to induce flowering in the plants. To better understand the results obtained, complementary analyses are necessary to investigate the possible causes of non-flowering in the evaluated plants.